2011
DOI: 10.15835/nbha3926172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drought Tolerance in Rapeseed Genotypes under Non Stress and Drought Stress Conditions

Abstract: Drought is a wide spread problem seriously influencing rapeseed (Brassica napus L.) production, mostly in dryland regions. This study was conducted to determine drought tolerance genotypes with superiority in different stressed environments. Twenty three rapeseed genotypes were tested in a split plot design based on randomized complete block design (RCBD) with four replications in two years (2008- 2009 and 2009-2010) at Seed and Plant Improvement Institute of Karaj, Iran. Seven drought resistance indices inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
4
10
0
Order By: Relevance
“…This is also approved by cluster analysis. Other researchers, using cluster analysis based on stress tolerance indices and genotypic classification, indicated that the results obtained from this method are consistent with the principal components analysis (Ahmadizadeh et al, 2012;Mohammadi et al, 2011;Rad and Abbasian, 2011). The clusteranalysis of 30 genotypes of wheat were placed into three separate groups (Parchin et al, 2013).…”
Section: Indexsupporting
confidence: 62%
“…This is also approved by cluster analysis. Other researchers, using cluster analysis based on stress tolerance indices and genotypic classification, indicated that the results obtained from this method are consistent with the principal components analysis (Ahmadizadeh et al, 2012;Mohammadi et al, 2011;Rad and Abbasian, 2011). The clusteranalysis of 30 genotypes of wheat were placed into three separate groups (Parchin et al, 2013).…”
Section: Indexsupporting
confidence: 62%
“…Development of cultivars with improved drought tolerance is of great importance in rapeseed breeding programs. Rapeseed cultivars have shown significant variation in terms of drought tolerance [2,3] and [4]. Responses to drought stress depend on genotype, intensity and duration of water deficit, weather conditions, growth and developmental stages of rapeseed [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, yield index (YI) was defined as ratio of the yield of a given genotype under stressful conditions to the average yield of all genotypes in the same conditions [13] and [14]. Previous studies demonstrated that STI, MP, GMP and MSTI are appropriate indices for screening drought tolerant rapeseed genotypes [2,3,4] and [15]. Water use efficiency (WUE) for yield is another major component to take into account for plant production under water-limited conditions, although the relationship between WUE and drought tolerance is complex and variable [16].…”
Section: Introductionmentioning
confidence: 99%
“…Canola is relatively poorly adapted to drought prone conditions (Wright et al, 1997) and its yield is often decreased if moisture stress occurred, particularly at reproductive stage (Ahmadi and Bahrani, 2009;Shirani Rad and Abbasian, 2011). The reduction in seed yield ranged from 19 -39% compared with well-watered control, when drought stress was imposed at reproductive stage (Gunasekara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%